Inclusive Learning: Freedom of Learning for Young Learner - Endah Windiastuti (Prodi Pendidikan Guru Pendidikan Anak Usia Dini, 2026)
This study aims to examine the implementation of differentiated learning in inclusive early childhood education through a case study at TK Budi Mulia Dua Sedayu, Bantul, Yogyakarta. Four respondents were involved, consisting of the principal, two classroom teachers, and one special assistant teacher (GPK). Research data were collected through in‑depth interviews, classroom observations, and analysis of lesson plans and Individualized Learning Program (PPI) documents. Data were analyzed through processes of reduction, categorization, and triangulation to ensure validity and accuracy of interpretation. The findings indicate that differentiated learning begins with systematic screening and developmental assessments, which then serve as the basis for designing PPIs tailored to the needs, strengths, and conditions of each individual child. The presence of GPKs and classroom management inspired by Montessori principles supports the creation of a safe, flexible, and inclusive learning environment that accommodates student diversity. The study also reveals challenges such as limited teacher competence in applying differentiation strategies, insufficient comprehensive training, and parental resistance to accepting assessment results. The novelty of this research lies in its integration of differentiated learning within Indonesia’s inclusive PAUD context—a topic that remains understudied—particularly in relation to the use of PPI as a primary instrument. Significantly, the study offers a replicable practical model to enhance the quality of inclusive PAUD services, strengthen support for children with special needs, and contribute to achieving SDG 4 on quality education for all children.Keywords – Special Needs; Inclusive; Differentiated Learning; Early Childhood Education; PAUD